Penggunaan Sistem Blockchain Di Perpustakaan Sekolah Dalam Meningkatkan Kinerja Guru Bahasa Indonesia Pasca Pandemi Covid-19 - Lorensius Eko Setiawan (Universitas Kristen Satya Wacana, 2024)
The school library is one of the important components in the educational ecosystem affected by the pandemic, including the private high school SMA XYZ in South Tangerang, which is the subject of this study. The research objective is to describe the effectiveness of the Blockchain system in accommodating data storage and its impact on efforts to improve the performance of Indonesian language teachers at SMA XYZ in utilizing the library. This study adopts a descriptive qualitative approach involving Indonesian language teachers and library staff. Data were collected through interviews and participatory observation. The collected data were validated through observation, documentation, and providing written questionnaires, administered directly in front of the researchers. If there were discrepancies in the data, further discussion with the sources would be conducted. Validated data were compared and summarized. The results of data analysis indicate that Indonesian language teachers have not maximized the use of the school library. The service system and data management in the library are also not optimal. The Blockchain system is proposed as an effort to improve teacher performance because it enables transparency, reliability, and security in information storage and exchange. In the context of the school library, the Blockchain system can be used to record and manage teachers' learning history, awards, and assessments by students and colleagues. Poorly organized book inventory management and borrowing processes make it difficult to utilize library facilities. The research findings indicate that the Blockchain system effectively addresses various challenges mentioned above.